Analisa Kinerja Guru Smk â€œKanada Sakura Indonesiaâ€ Pekanbaru Sebagai Dampak Dari Lingkungan Kerja Di Sekolah - Syahsudarmi, Siti (Sekolah Tinggi Ilmu Ekonomi Riau, 2023)
The research was conducted at the Canadian Sakura Indonesia Vocational Â Â School in Pekanbaru. The aim of this research is to determine the influence of the work environment on teacher performance at the Sakura Indonesia Canadian Vocational School in Pekanbaru. Data analysis in this research uses quantitative methods. The sample taken in this research was 32 people, and the t-count results were greater than the t-table (5.845>2.04227). So it can be concluded that there is a significant influence between the work environment on teacher performance. Then the simple linear equation is Y = 11.760 + 0.606X. From the existing regression equation it can be concluded that the regression coefficient of bx is positive. This shows that if the work environment variable is increased the equation will also lead to an increase in the teacher performance variable. The R Square result of 0.532 shows that the work environment influences teacher performance by 53.2% and the remaining 46.8% is influenced by other independent variables which were not observed in this study